PENGARUH PUPUK HAYATI TERHADAP PERTUMBUHAN TANAMAN, DAN POPULASI BAKTERI PELARUT KALIUM PADA TANAMAN TEBU (Saccharum officinarum L.) - Delma Aida Syavitri; Cahyo Prayogo; Sandi Gunawan (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
Biofertilizer applications are needed to improve soil quality such as soil productivity and increasing the efficiency of the fertilization. Availability of nutrients in the soil is affected by microbes found in the soil. Soil microbes reproduce themselves and active in supplying nutrients to plants by releasing nutrients that are bound to be available to plants. The aim of this research was to observe and analyze the effect of biofertilizer on sugarcane growth and its effect on the population of potassium solubilizing bacteria. Results showed that The application of basic fertilizer combined with biofertilizer has a significant effect on the growth of sugarcane both in plant height and diameter of the stem. In the parameters of plant height, the best treatment was A5 which was a combination of anorganic fertilizer + 200% biofertilizer same as the other plant growth parameter which was stem diameter. Then on the production parameters, fresh plant weight and root weight, best treatment was A5. As for the parameters of potassium solubilizing bacteria, the best treatment that increased population was treatment A4 which was basic fertilizer combined with 150% biofertilizers. In total soil bacteria, the various application doses of biofertilizers did not have a significant effect. However, there was an increase of 0,49% in treatment A5 (basic fertilizer+200% biological fertilizer) compared to control (A1). The application of biofertilizer also did not have a significant effect on the parameters of organic matter and soil water content